Rescuing Europe - Hans-Werner Sinn (CESifo Forum, 2010)
After the recent global financial crisis several countries on the eurozone's south-western periphery, in particular Greece, Spain, Portugal and Ireland, have faced severe difficulties involving the risk of sovereign debt defaults and a new banking crisis. Other EU countries, above all France, were indirectly affected by this crisis, and some eastern European countries are also endangered. Although the EU has tried to contain the euro crisis with extensive rescue operations that have turned the no-bail out philosophy of the Maastricht Treaty on its head, in summer 2010 the danger was not yet over. Obviously, the construction of the eurozone, in particular the rules of conduct for the participating countries, needs to be reconsidered. Yet the euro should not be given up. The euro itself is indispensible for Europe. During the financial crisis it has protected its members from internal exchange rate shocks, it has reduced the European transactions costs for trade, and it is a necessary ingredient of further European integration. Nevertheless, Hans-Werner Sinn argues that the euro has not been as beneficial for all European countries as has often been claimed. The euro has shifted Europe's growth forces from the center to the periphery. It has not been particularly beneficial for Germany, for example, and because of a lack of proper private and public debt constraints, it has stimulated the periphery of Europe up to the point of overheating, with ultimately dangerous consequences for European cohesion. The current crisis has not put an end to this development. It has flipped a toggle switch that will shift the forces of growth back from the periphery to the center, although the EU rescue measures counteract this. Hans-Werner Sinn criticizes these measures because of the moral hazard effects they generate and proposes a new political design for a more prosperous and stable development of the eurozone.
Keywords: F34; G01; 330; Finanzmarktkrise; Geldpolitik; EU-Stabilitätspakt; Euro; Eurozone; Europäische Wirtschafts- und Währungsunion